Utilizing Natural Materials to Stimulate Creativity in Children Aged 5–6 Years: A Classroom Action Research Study in Early Childhood Education - Fitri Febri Handayani; Triyana Triyana; Sefriyanti Sefriyanti; Amalia Husna; Husnul Hafidhoh (STAI Auliaurrasyidin Tembilahan, 2026)
Early childhood education plays a crucial role in stimulating creativity as a foundation for developing high-quality human resources. Children’s creativity can be fostered from an early age through meaningful and contextual learning experiences, one of which involves the use of natural materials closely connected to children’s everyday environments. This study aimed to examine improvements in creativity among children aged 5–6 years through the use of natural-material-based learning media in early childhood education settings. This study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, implemented in two cycles. The participants consisted of 25 children from Group B at PAUD Kasih Ibu, Kempas District. Data were collected through structured observation and field notes, while data analysis used percentage techniques to identify changes in children’s creativity across action cycles. The findings indicate that the use of natural materials effectively and gradually enhances children’s creativity. Improvements were observed in children’s abilities to explore, imagine, try new ideas, and express ideas independently. These results suggest that natural materials function as effective contextual learning media that support creativity development in early childhood. Therefore, this study provides practical implications for early childhood educators in designing creative, contextual, and sustainable learning experiences.